A Non-Invasive Heart Rate Measurement Method Is Improved by Placing the Electrodes on the Ventral Side Rather Than the Dorsal in Loggerhead Turtles - Kinoshita, Chihiro; Saito, Ayaka; Kawai, Megumi; Sato, Katsufumi; Sakamoto, Kentaro Q. (Frontiers in Physiology, 2022)
Heart rate measurement is an essential method for evaluating the physiological status of air-breathing diving animals. However, owing to technical difficulties, most marine animals require surgical implantation of the device to record an electrocardiogram (ECG) in water, limiting the application of this approach in a wide range of marine animals. Recently, a non-invasive system was reported to measure the ECG of hard-shelled sea turtles by pasting the electrodes on the dorsal side of the shell, although the ECG obtained from the moving turtle contains noise produced by muscle contraction. Here, we report that clear ECGs can be obtained by placing the electrodes on the ventral side rather than the dorsal side in loggerhead sea turtles. Using our method, clearer ECG signals were obtained without noise, even when turtles are swimming. According to the anatomical features, the electrode position on the ventral side is closer to the heart than the dorsal side, minimizing the effects of noise generated by the skeletal muscle. This new biologging technique will elucidate the functioning of circulatory system of sea turtles during swimming and their adaptabilities to marine environments. This article is part of the theme issue ‘Methods and Applications in Physio-logging’.